2020
DOI: 10.1590/0034-7167-2019-0873
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy of health professionals in hand hygiene practice: is it possible to measure?

Abstract: Objective: To identify in the literature the tools used to measure self-efficacy of health professionals in hand hygiene. Methods: Integrative literature review carried out by consulting the databases PubMed, Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Europe PubMed Central, and Science Direct using the descriptors Self Efficacy, Hand Hygiene, and Health Personnel. Results: Six articles, all of which with observational design, were selected. It was possible to infer that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Each additional meter, which must be covered by the health professional to reach a sink, decreased the likelihood of HH by approximately 10% [6]. Likewise, a study carried out in a pediatric and neonatal ICU in the United Kingdom found that, as the visibility of sinks increased, the number of HH actions also increased [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Each additional meter, which must be covered by the health professional to reach a sink, decreased the likelihood of HH by approximately 10% [6]. Likewise, a study carried out in a pediatric and neonatal ICU in the United Kingdom found that, as the visibility of sinks increased, the number of HH actions also increased [24].…”
Section: Discussionmentioning
confidence: 99%
“…Different factors may be related to low HH adherence, among them, health services with inadequate physical structure, including poorly located sinks [6,19,20], inoperative dispensers of alcohol-based handrubs and without arms reach [12,19,20], use of procedure gloves [21], lack of training, among others [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations